Suppression of Inflammatory Cytokines Expression With Bitter Melon (Momordica Charantia) in TNBS-Instigated Ulcerative Colitis - Semiz, Asli; Acar, Ozden Ozgun; Cetin, Hulya; Semiz, Gurkan; Sen, Alaattin (Sciendo, 2020)
Background and Objective: This study was aimed to elucidate the molecular mechanism of Momordica charantia (MCh), along with a standard drug prednisolone, in a rat model of colitis induced by trinitrobenzene sulfonic acid (TNBS). Methods: After the induction of the experimental colitis, the animals were treated with MCh (4 g/kg/day) for 14 consecutive days by intragastric gavage. The colonic tissue expression levels of C-C motif chemokine ligand 17 (CCL-17), interleukin (IL)-1 beta, IL-6, IL-23, interferon-gamma (IFN-gamma), nuclear factor kappa B (NFkB), and tumor necrosis factor-alpha (TNF-alpha), were determined at both mRNA and protein levels to estimate the effect of MCh. Besides, colonic specimens were analyzed histopathologically after staining with hematoxylin and eosin. Results: The body weights from TNBS-instigated colitis rats were found to be significantly lower than untreated animals. Also, the IFN-gamma, IL-1 beta, IL-6, Il-23, TNF-alpha, CCL-17, and NF-kB mRNA and protein levels were increased significantly from 1.86-4.91-fold and 1.46-5.50-fold, respectively, in the TNBS-instigated colitis group as compared to the control. Both the MCh and prednisolone treatment significantly reduced the bodyweight loss. It also restored the induced colonic tissue levels of IL-1 beta, IL-6, IFN-gamma, and TNF-alpha to normal levels seen in untreated animals. These results were also supported with the histochemical staining of the colonic tissues from both control and treated animals. Conclusion: The presented data strongly suggests that MCh has the anti-inflammatory effect that might be modulated through vitamin D metabolism. It is the right candidate for the treatment of UC as an alternative and complementary therapeutics.
Sen, Alaattin/0000-0002-8444-376X;
Keywords: Momordica charantia; Ulcerative Colitis; Inflammatory Bowel Disease; Anti-Inflammatory; Inflammatory Cytokines; Vitamin D; CYP27B1; Trinitrobenzenesulfonic Acid; Immunohistochemistry; Alternative and Complementary Therapeutics